Autistic traits in a sample of adult patients with schizophrenia: prevalence and correlates. Issue 1 (20th March 2018) - Barlati, S.; Deste, G.; Gregorelli, M.; Vita, A.
Abstract: Background: Schizophrenia and autism spectrum disorder (ASD) are currently conceptualized as distinct disorders. However, the relationship between these two disorders has been revisited in recent years due to evidence that they share phenotypic and genotypic expressions. This study aimed to identify ASD traits in patients with schizophrenia, and to define their demographic, psychopathological, cognitive and functional correlates. Method: Seventy-five schizophrenia patients (20 females, mean age 42 ± 12) were evaluated with the Autism Diagnostic Observation Schedule (ADOS) and the Autism Diagnostic Interview-Revised (ADI-R). Participants were also assessed with clinical, neuropsychological, and psychosocial functioning measures. Results: Of the 75 patients, 47 were negative to all the autism scales administered (ADOS-TOT-NEG), 21 patients were positive to the ADOS Language sub-domain (ADOS-L-POS), 21 patients were positive to the ADOS Reciprocal Social Interaction (RSI) sub-domain (ADOS-RSI-POS), 14 patients were positive to the ADOS Total scale (ADOS-TOT-POS), and nine patients were positive to the ADI-R scale (ADI-R-POS). Demographic (duration of illness), psychopathological (negative symptoms and general psychopathology), and cognitive (working memory and processing speed) differences emerged between schizophrenic patients with and without ASD traits, while no differences in psychosocial functioning were detected. Results of this study indicate the existence, in a sample of patients with a diagnosis of schizophrenia, of a distinct group of subjects with ASD features, characterized by specific symptomatological and cognitive profile. Conclusions: These findings may contribute to better characterize patients with schizophrenia in order to develop new procedures and therapeutic tools in a more personalized perspective.